Exploring the interaction between epidermal growth factor receptor tyrosine kinase and some of the synthesized inhibitors using combination of in-silico and in-vitro cytotoxicity methods - Rezvan Rezaee Nasab; Mahboubeh Mansourian; Farshid Hassanzadeh; Mohsen Shahlaei (Wolters Kluwer Medknow Publications, 2018)
Quinazoline derivatives are potent inhibitors of human epidermal growth factor receptor (EGFR) as anticancer agents. In this study, the cytotoxic effects of a new series of synthesized quinazoline derivatives were evaluated using MTT assay against MCF-7 and HT-29 cell lines. Using molecular docking, the binding modes of all compounds were analyzed at the binding site of EGFR. Based on the results, the compounds L1, L2, L4, L5, L6, L7, L10, L15, and L18 may be promising EGFR inhibitors based on docking score and hydrogen bonds. Consistent with the experimental data, Met769 is recognized as a key residue in the binding of potential inhibitors. According to the MTT cytotoxicity assays, Lipinski's rule of five (RO5), absorption, distribution, metabolism, excretion, and toxicity (ADMET) parameters, and docking studies, three compounds L4, L15, and L10 with IC50 values of 80, 60, and 1 μM against the MCF-7 were selected for further comparative assessments. The dynamics of free EGFR, and selected ligand-EGFR complexes were investigated using molecular dynamics (MD) simulation studies. The results indicated that the three compounds bound to EGFR active site in a stable manner during the simulation through the formation of new hydrogen bonds with Phe699, Leu694, Gly700, Lys721, Met769, Arg817, and Asp831 with the superiority of compound L15. These features can promote future drug candidate designing to produce better derivatives in the search for the anticancer agents.